2021
DOI: 10.1007/s11136-021-02998-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with impaired quality of life three months after being diagnosed with COVID-19

Abstract: Purpose To assess patient characteristics associated with health-related quality of life (HR-QoL) and its mental and physical subcategories 3 months after diagnosis with COVID-19. Methods In this prospective multicentre cohort study, HR-QoL was assessed in 90 patients using the SF-36 questionnaire (36-item Short Form Health Survey), which consists of 8 health domains that can be divided into a mental and physical health component. Mental health symptoms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 48 publications
5
28
1
1
Order By: Relevance
“…The prevalence of PTSD in this study was in line with studies with similar populations 2-12 months after hospitalization for COVID-19 (10,11,(13)(14)(15)(16)(17), but lower than in some populations with more severe disease (8,12,18,25). However, rates of PTSD disorders following COVID-19 as low as 3.8% has been reported in combined hospitalized/non-hospitalized samples (26).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence of PTSD in this study was in line with studies with similar populations 2-12 months after hospitalization for COVID-19 (10,11,(13)(14)(15)(16)(17), but lower than in some populations with more severe disease (8,12,18,25). However, rates of PTSD disorders following COVID-19 as low as 3.8% has been reported in combined hospitalized/non-hospitalized samples (26).…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies have reported significant PTSD symptoms during and after hospitalization for COVID-19 among 2-40 % of patients with follow-up of 1-6 months, and just recently 12-15 months, in cross-sectional or cohort studies (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Prevalence rates vary according to time after acute COVID-19, assessment method, sample selection, and geographical region.…”
Section: Introductionmentioning
confidence: 99%
“…Disease complications and post-COVID/long COVID syndromes are responsible for the deterioration of the general condition and cardiorespiratory fitness (CRF) of convalescents due to: slow regression of inflammatory changes in the lungs and persistence of respiratory failure with dyspnea, chronic cough, and development of interstitial pulmonary fibrosis [4]; cardiological complications, including myocarditis and ventricular arrhythmias [5]; thromboembolic events, including pulmonary embolism [6]; neurological complications, such as myopathy and neuropathy, associated with prolonged immobilization and leading to motor disabilities and limitations in performing daily activities [7]; persistent osteoarticular pain [3]; chronic fatigue or muscle weakness [3]; depression and anxiety worsening the quality of life and physical effort tolerance [3,8]; and exacerbation of chronic diseases. Therefore, comprehensive CR of symptomatic patients with a history of COVID-19 is recommended by experts worldwide [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Other PROMs assessing HRQoL, e.g., SF-12 30 , 15D 31 , or SF-36 32 , have been also used in individuals with post-COVID symptoms. All these studies reported the same results, people with long-COVID exhibit reduced HRQoL.…”
Section: Discussionmentioning
confidence: 99%